(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
The essay gives a collection and a complete transcription of Giuseppe Rovani’s autograph letters found till now (with some novelties, particularly thanks to Archivio Lechi of Brescia). Through a comment constantly related with Carlo Dossi’s biographical documents (especially Rovaniana, and Note azzurre), we shall follow Rovani’s librarian career in Braidense and we shall examine his large circle of Milanese friends as well as his work as a journalist and writer.